Salivary cortisol in longitudinal associations between affective symptoms and midlife cognitive function: A British birth cohort study. (July 2022) - John, Amber; Desai, Roopal; Saunders, Rob; Buckman, Joshua E.J.; Brown, Barbara; Nurock, Shirley; Michael, Stewart; Ware, Paul; Marchant, Natalie L.; Aguirre, Elisa; Rio, Miguel; Cooper, Claudia; et al.
Abstract: Affective disorders are associated with accelerated cognitive ageing. However, current understanding of biological mechanisms which underlie these observed associations is limited. The aim of this study was to test: 1) Whether cortisol acts as a pathway in the association between depressive or anxiety symptoms across adulthood and midlife cognitive function; 2) Whether cortisol is associated with later depressive or anxiety symptoms, and cognitive function. Data were used from the National Child Development Study (NCDS), a sample of infants born in mainland UK during one week of 1958. A measure of the accumulation of affective symptoms was derived from data collected from age 23 to 42 using the Malaise Inventory Scale. Salivary cortisol measures were available at age 44–45. Cognitive function (memory, fluency, information processing) and affective symptoms were assessed at the age of 50. Path models were run to test whether salivary cortisol explained the longitudinal association between depressive or anxiety disorder symptoms and cognitive function. Direct effects of affective symptoms are shown across early to middle adulthood on cognitive function in midlife (memory and information processing errors). However, there were no effects of affective symptoms on cognitive function through cortisol measures. Additionally, cortisol measures were not significantly associated with subsequent affective symptoms or cognitive function at the age of 50. These results do not provide clear evidence to suggest that cortisol plays a role in the association between affective symptoms and cognitive function over this period of time. These findings contribute to our understanding of how the association between affective symptoms and cognitive function operates over time. Highlights: Biological mechanisms underlying links between depression and cognition are unclear. The aim of this study was to test the role of cortisol in this association. These results provide no evidence that cortisol mediates this association. Findings contribute to understanding of how this association operates over time.